[62]Tetradecaphyrin and Its Mono‐ and Bis‐ZnII Complexes. Issue 41 (17th August 2016) - Yoneda, Tomoki; Soya, Takanori; Neya, Saburo; Osuka, Atsuhiro
Abstract: A coiled structure of meso ‐pentafluorophenyl‐substituted [62]tetradecaphyrin1 was revealed by X‐ray structural analysis. Synthetic protocols were devised to form mono‐ and bis‐Zn II complexes, 1 Zn and1 Zn2, selectively. The former displayed a trigonal‐bipyramidal pentacoordinated Zn II ion as a rare case and a cyclic voltammogram exhibiting eleven reversible redox waves. The latter showed a Ci ‐symmetric structure with modest Hückel aromaticity owing to a 62 π‐electronic circuit as the largest aromatic molecule to date. Abstract : Zn and the art of macrocycle maintenance : [62]Tetradecaphyrin and its mono‐ and bis‐Zn II complexes have been synthesized and characterized. The mono‐Zn II complex displays a trigonal‐bipyramidal pentacoordination as a rare case and eleven reversible redox potentials. The bis‐Zn II complex has been shown to be the largest Hückel aromatic molecule reported to date.